The Role of the Medial Septum—Associated Networks in Controlling Locomotion and Motivation to Move - Mocellin, Petra; Mikulovic, Sanja (Frontiers in Neural Circuits, 2021)
The Medial Septum and diagonal Band of Broca (MSDB) was initially studied for its role in locomotion. However, the last several decades were focused on its intriguing function in theta rhythm generation. Early studies relied on electrical stimulation, lesions and pharmacological manipulation, and reported an inconclusive picture regarding the role of the MSDB circuits. Recent studies using more specific methodologies have started to elucidate the differential role of the MSDB’s specific cell populations in controlling both theta rhythm and behaviour. In particular, a novel theory is emerging showing that different MSDB’s cell populations project to different brain regions and control distinct aspects of behaviour. While the majority of these behaviours involve movement, increasing evidence suggests that MSDB-related networks govern the motivational aspect of actions, rather than locomotion per se. Here, we review the literature that links MSDB, theta activity and locomotion and propose open questions, future directions and methods that could be employed to elucidate the diverse roles of the MSDB-related networks.